Reoperative Aortic Arch Surgery under Mild Systemic Hypothermia: Two-Center Experience - Risteski, Petar; Radacki, Isabel; Zierer, Andreas; Lenos, Aris; Moritz, Anton; Urbanski, Paul P. (AORTA, 2021)
Background The aim of the study was to assess the indications, surgical strategies, and outcomes after reoperative aortic arch surgery performed generally under mild hypothermia.Methods Ninety consecutive patients (60 males, mean age, 55 ± 16 years) underwent open reoperative aortic arch surgery after previous cardiac aortic surgery. The indications included chronic-progressive arch aneurysm (55.5%), chronic aortic dissection (17.8%), contained arch rupture (16.7%), and graft infection (10%). The reoperation was performed through a repeat sternotomy (96%) or clamshell thoracotomy (4%) using antegrade cerebral perfusion under mild systemic hypothermia (28.9 ± 2.5°C) in all except three patients.Results The surgery comprised hemiarch or total arch replacement in 41 (46%) and 49 (54%) patients, respectively. The distal extension included classic or frozen elephant trunk technique, each in 12 patients, and total descending aorta replacement in 4 patients. Operative mortality was 6 (6.7%) among all patients, with age identified as the only independent predictor of operative mortality (p = 0.05). Permanent and transient neurologic deficits occurred in 1% and 9% of the patients, respectively. Estimated survival at 8 years was 59 ± 8% with advanced heart failure predictive for late mortality (p = 0.014). Freedom from second reoperation or intervention on the aorta was 78 ± 6% at 8 years, with most of these events occurring downstream in patients with chronic degenerative aneurysms.Conclusion Aortic arch reoperations performed using antegrade cerebral perfusion under mild systemic hypothermia offer favorable operative outcomes with an exceptionally low rate of neurologic morbidity without any difference between hemiarch and complex arch procedures.
Keywords: aortic arch surgery; reoperation; mild hypothermia